Dirac Quantization for Interaction Lagrangian with Time Derivative Terms - Syaefudin Jaelani; Anto Sulaksono (Jurnal Matematika & Sains, 2012)
The presence of the second order time derivative terms in interaction Lagrangian density of fermions system precludes to apply directly the quantization procedure to its canonical Hamiltonian. Field transformation is used here to handle this problem, so that the transformed Hamiltonian density can be quantized by using Dirac quantization procedure. We obtain the two sets primary constraints which are used to construct Dirac matrix, bracket relation as well as the transformed Hamiltonian. Using this transformed Hamiltonian, the 00-component of energy momentum tensor as well as the equation of state of the system are calculated. Keywords: Field transformation, Canonical Hamiltonian, Transformed Hamiltonian density, Dirac quantization procedure. Â  Kuantisasi Dirac untuk Lagrangian Interaksi dengan Suku-Suku Turunan terhadap Waktu Abstrak Keberadaan suku turunan orde kedua terhadap waktu pada kerapatan Lagrangian interaksi pada sistem fermion menghalangi penggunaan prosedur kuantisasi secara langsung pada Hamiltonian kanonik sistem. Transformasi medan digunakan disini untuk mengatasi masalah tersebut, sehingga kerapatan Hamiltonian hasil transformasi dapat dikuantisasi dengan menggunakan prosedur kuantisasi Dirac. Kami memperoleh dua buah kendala primer yang digunakan untuk membentuk matriks Dirac, relasi braket dan memperoleh Hamiltonian yang siap dikuantisasi. Dengan menggunakan Hamiltonian ini, komponen-00 tensor momentum energi dan persamaan keadaan sistem dapat diperoleh. Kata kunci: Ttransformasi medan, Hamiltonian kanonik, Kerapatan Hamiltonian hasil transformasi, Prosedur kuantisasi Dirac.